2001
DOI: 10.1046/j.1524-475x.2001.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of apoptosis in keloids and a comparative study on apoptosis between keloids, hypertrophic scars, normal healed flat scars, and dermatofibroma

Abstract: Recent studies have suggested that the regulation of apoptosis during wound healing is important in scar establishment and the development of pathological scarring. In this study, we demonstrate that keloid fibroblasts can be identified as apoptotic cells because of their highly condensed chromatin and discrete nuclear fragments. To further reveal the phenomenon of apoptosis, we quantified the number of terminal deoxynucleotide transferase-mediated dUTP nick-end labeling (TUNEL)-positive cells in surgically re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 28 publications
2
52
0
Order By: Relevance
“…This latter proposition, however, lacks conclusive evidence to date. Recent papers have shown data supporting the possibility that there is increased survival of fibroblasts from keloid scars in response to signals that would normally induce apoptosis (Chodon et al, 2000;Ishihara et al, 2000), while other studies suggest a possible imbalance between proliferation and apoptosis in keloids and hypertrophic scars but without clear evidence of decreased levels of apoptosis (Akasawa et al, 2001;Luo et al, 2001). The expression of genes that are protective against apoptosis, such as Bcl-2, has been shown to be increased in keloids and hypertrophic scars, suggesting a mechanism through which an imbalance between proliferation and apoptosis may be achieved (Teofoli et al, 1999).…”
Section: Myofibroblasts During Normal Healing In the Skinmentioning
confidence: 99%
“…This latter proposition, however, lacks conclusive evidence to date. Recent papers have shown data supporting the possibility that there is increased survival of fibroblasts from keloid scars in response to signals that would normally induce apoptosis (Chodon et al, 2000;Ishihara et al, 2000), while other studies suggest a possible imbalance between proliferation and apoptosis in keloids and hypertrophic scars but without clear evidence of decreased levels of apoptosis (Akasawa et al, 2001;Luo et al, 2001). The expression of genes that are protective against apoptosis, such as Bcl-2, has been shown to be increased in keloids and hypertrophic scars, suggesting a mechanism through which an imbalance between proliferation and apoptosis may be achieved (Teofoli et al, 1999).…”
Section: Myofibroblasts During Normal Healing In the Skinmentioning
confidence: 99%
“…It has been known that extensive enlargement of keloid lesions is due to KF proliferations, collagen depositions, and cellular migrations. [3][4][5] In order to totally treat keloid lesions, we agree that MC must be combined with keloid surgery that removes the existing fibrous tissue material which richens by collagen bundles, such as previously reported by many authors. 15,16,22,23 In this combination, unremoving KF and collagen bundles on the surface of debulking lesions of preexisting keloid can be prevented to grow and to be prevented to relapse.…”
Section: Discussionmentioning
confidence: 65%
“…17 Our results showed that 120 uM MC can inhibit proliferation and migration of KF FIGURE 1. This finding is important because continuously enlargement of keloid lesion is under responsible of high proliferation rate of KF [3][4][5] and high migration ability to invade surrounding normal tissue. 8 Application 120 uM MC for 72 hours had no significantly different effect in proliferation index and inhibition of cellular migration than 24 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…88 This process is also mediated in part by the induction of apoptosis, whereas in aberrant scarring, such as NVAMD, inadequate apoptosis may occur. [118][119][120] Similar to that in the earlier stages of repair, the bone marrow is also intrinsically involved in fibrogenesis. Fibrocytes in the peripheral blood are derived from mesenchymal stem cells in the bone marrow and are involved not only in scar tissue deposition but are also thought to have a role in the inflammatory and proliferative (NV) phases of repair.…”
Section: Subretinal Neovascularisationmentioning
confidence: 98%